Interpreting ASEAN developmental regionalism through discursive institutionalism - Elumbre, Adonis L. (Kasarinlan: Philippine Journal of Third World Studies, 2014)
While literature abound on the history and current state of regionalism in Southeast Asia in the form of the Association of Southeast Asian Nations (ASEAN), much still needs to be done on explaining the dynamics of institutional change and continuity in the organization. One of the approaches that has the potential for reframing the existing empirical research is discursive institutionalism. Defined as a new variant of the institutionalist framework, discursive institutionalism emphasizes the importance of “the substantive content of ideas and the interactive processes of discourse in institutional contexts” (Schmidt 2010, 3). This paper is an attempt to apply discursive institutionalism to explain developmental regionalism in ASEAN. In view of competing discourses about regionalism, a more coherent narrative of the ASEAN that highlights critical junctures and incremental change in its conceptualization and communication shall be presented. A discursive institutionalist reading is expected to yield insights on the restraining and enabling contexts of ASEAN itself—an exercise in retrospective interpretation that could aid academic discussions and policy debates on the present direction of regional community-building.